PERKEMBANGAN INDEKS GINI DI PROPINSI DATI I JAWA BARAT - Sutyastie Soemitro Remi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1998)
The problem of inequality in income distribution has for long been a focus of research interest. There is also a high possibility that this problem is responsible for the social stress and disturbances. Inorder to address this issue, there is a need to approach it through the gini index both over time and between regions, rural-urban, and also between groups in order to get an empirical observation, particularly in provincial level of Java. We can draw a general conclusion that the inequality in income distrilmtion in West Jam is low. In this connection, there is a tendency that the degree of inequality is high inareas the middle of development is relatively higher and then in urban areas. Thus, development policies aimed at improving on community income distribution should therefore, prioritize these areas.